Apache II score in predicting surgical outcome in patients of secondary peritonitis: a prospective and observational study - Jeelani, Shaukat; Aziz, Asgar; Kumar, Irshad A.; Dar, Waseem A.; Nowreen, Farzanah (International Journal of Research in Medical Sciences, 2020)
Background: Peritonitis is defined as inflammation of the serosal membrane that lines the abdominal cavity and the organs contained therein. Secondary peritonitis presenting as acute generalized peritonitis is a common surgical emergency often associated with significant morbidity and mortality. Many scoring systems have been found useful in predicting the outcome in critically ill patients, thus allowing application of resources for effective use. Amongst them acute physiology and chronic health evaluation score (APACHE II), have a strong relationship to the outcome than previous groupings without consideration for systemic effect of the intra-abdominal sepsis. Methods: This study was conducted in the Department of General surgery, Sri Maharaja Hari Singh (SMHS) Hospital an associated hospital with the Government Medical College Srinagar, J&K, India. The prospective study was conducted over a period from October 2016 to September 2018 (Two Year) on 108 patients diagnosed with secondary peritonitis. Data was collected and analysed using SPSS v 20. Results: study included 108 patients with males involving 74.1% (80). The mean age of our study was 34 yr. (2-88 yr.), and 21-40 yr. (44.5%) group was mostly involved. Pain abdomen was present in 100% patients followed by nausea/vomiting (88%). Higher the APACHE VII score higher were post-operative complications (31+ score group 100%), mortality (31+ score group 100%) and less hospital stay (31+ score group 1.5 days) due to increased mortality. Conclusions: APACHE II score correlated well with postoperative complications, outcome, hospital stay. However, in patients with very high Apache score more than 30, the mean duration of hospital stay is less due to associated increased mortality during early Hospital stay.